ANALISIS PENDAPATAN DAN KELAYAKAN USAHA PETERNAKAN AYAM RAS PETELUR SURYADI FARM DI DESA CIKOWANG KECAMATAN MANGARABOMBANG KABUPATEN TAKALAR - Irmayani, Irmayani (Program Studi Peternakan Universitas Muhammadiyah Sidenreng Rappang, 2026)
This study aims to determine the amount of income and business feasibility system obtained from the business of breeding laying hens in Suryadi Farm located in Cikowang Village, Mangarabombang District, Takalar Regency. Determination of the location of this study is determined intentionally (purposive). This study was conducted in July-August 2025. This type of research uses descriptive quantitative research with a case study approach to provide a comprehensive overview of the overall income structure and level of business feasibility. The type of data used is primary data sourced from direct interviews with livestock owners include business results and other costs. While the use of secondary data is data obtained from relevant agencies such as a general description of the location and state of the research area. The population in the study is 4 cage type batteries, each of which has a different population level. Sampling in the study was conducted by Purposive sampling, which is based on certain criteria set by the researcher. The sample used is cage 1 with the highest population of 3,100 and will be analyzed in one period in 2024. Based on the results of research analysis, the net income obtained by laying hens is Rp588, 593, 087 in one production period. This value indicates a very good financial performance. The results of the feasibility analysis carried out on the indicators of R/C Ratio 1.57, BEP price 31,600 BEP production 21,885, and ROI 25.4% are in a very favorable condition and feasible to run for the long term.